THE IMPACT OF REWARDS AS MOTIVATION ON JOB SATISFACTION IN A QUANTITY SURVEYING CONSULTANT FIRM - Siti Nur Aishah Mohd Noor; Nadzirah Zainordin (INTERNATIONAL JOURNAL OF MODERN TRENDS IN SOCIAL SCIENCES (IJMTSS), 2024)
Motivation shows an important part in all private and public organization. An organization cannot run and cannot attain their desired goals and objectives without motivating their employees. The main objective of this research is to examine intrinsic and extrinsic motivation and the effects on employees’ job satisfaction, particularly in quantity surveyor consultant firm. The questionnaires were distributed via an online platform to all quantity surveyor employees in a small quantity surveyor firm, with permission from Human Resources Manager in the company. The questionnaire consists of 3 sections where section A for respondent’s demographic profile, Section B for accessing motivation as perceived important for employees and Section C for Job Satisfaction Survey. Data collection were collected within 3 days after distribution of questionnaire via employees’ email. Data collected then were screened for normality and linearity checking and then were analyzed using descriptive analysis, correlation and reliability analysis. Finding from this research shows that, employees ranked extrinsic rewards highest were festival bonus and incentives while for intrinsic rewards, recognition was ranked highest followed by appreciation. On the other hands, job satisfaction section, nature of works, co-workers and operating procedure in the company seems to be the most satisfied condition among employees in the company. This research concluded that, even though there was a moderate negative association between rewards and job satisfaction, the other factors may have influenced job satisfaction among quantity surveyor in this company.